1997
DOI: 10.1097/00001756-199705060-00012
|View full text |Cite
|
Sign up to set email alerts
|

NGF involvement in pain induced by chronic constriction injury of the rat sciatic nerve

Abstract: Chronic constriction injury (CCI) of the rat sciatic nerve, which within 3 days induces thermal and mechanical hyperalgesia and mechanical allodynia, is used as a model for pain resulting from nerve injury. Involvement of nerve growth factor (NGF) in the development of this hyperalgesia is suggested by the increase in the level of mRNA encoding NGF in cells in the injured area and in dorsal root ganglia at the level of the lesion and the greatly increased NGF levels (determined by ELISA) in the ganglia ipsilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
71
0
4

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(78 citation statements)
references
References 10 publications
3
71
0
4
Order By: Relevance
“…However, in recent years, growing evidence supports the hypothesis that a block of NGF action could provide effective pain relief in this chronic pain condition. In the CCI model, an increase of NGF levels is observed in the cells of the injured area and in dorsal root ganglia at the level of the lesion, suggesting the involvement of NGF in the development of hyperalgesia in this model of neuropathic pain (24). Direct administration of NGF into the sciatic nerve induces hyperalgesia in rats (26), whereas NGF inhibition reduces thermal and mechanical hyperalgesia in CCI model (24,27,46), partial nerve transection (28) and partial transection of the spinal cord (47).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, in recent years, growing evidence supports the hypothesis that a block of NGF action could provide effective pain relief in this chronic pain condition. In the CCI model, an increase of NGF levels is observed in the cells of the injured area and in dorsal root ganglia at the level of the lesion, suggesting the involvement of NGF in the development of hyperalgesia in this model of neuropathic pain (24). Direct administration of NGF into the sciatic nerve induces hyperalgesia in rats (26), whereas NGF inhibition reduces thermal and mechanical hyperalgesia in CCI model (24,27,46), partial nerve transection (28) and partial transection of the spinal cord (47).…”
Section: Discussionmentioning
confidence: 78%
“…On one hand, NGF exerts neuroprotective and trophic action on peptidergic small-diameter dorsal root ganglia cells, reversing many of the histological changes after nerve injury (4,22), and regulates the collateral sprouting of intact nociceptive sensory axons after denervation (23). On the other hand, peripheral neuropathic pain is correlated with elevated NGF levels (24,25), and direct administration of NGF into the sciatic nerve produces hyperalgesia (26) Moreover, NGF function inhibition results in analgesia in different neuropathy-related pain protocols, such as chronic constriction injury and partial sciatic nerve transection (27,28).…”
mentioning
confidence: 99%
“…Further evidence for the involvement of peripheral nerve fibers came from Kerr et al who demonstrated the absence of NGF mediated hyperalgesia in mice lacking expression of Kv1.8 a sodium ion channel found on primary afferent neurons (Kerr et al 2001). Finally, Herzberg et al reported using the chronic constriction injury (CCI) model of neuropathic pain that the application of NGF antiserum at the site of the ligatures delayed the appearance of hyperalgesia (Herzberg et al 1997). …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the pathogenic mechanisms of the abnormal hyperexcitability of the primary sensory neurons are unclear. Concentration of nerve growth factor (NGF) in DRG was reported to increase after the artificial nerve injury (9), and injection of exogenous NGF into healthy rats induced hyperalgesia (16). These reports suggest that NGF correlates with the pathogenesis of neuropathic pain.…”
mentioning
confidence: 99%